Negative electrode material for lithium ion battery and preparation method and application thereof

CN123017944APending Publication Date: 2026-10-30QINGDAO XINTAIHE ENERGY MATERIALS CO LTD
View PDF 6 Cites 0 Cited by

Patent Information

Application Number
CN202611335346.6
Authority / Receiving Office
CN · China
Patent Type
Applications(China)
Current Assignee / Owner
Filing Date
2026-08-31
Publication Date
2026-10-30

AI Technical Summary

Technical Problem

但该方案中碳质材料与非碳质材料混合于同一复合层中,未形成分层结构

Benefits of technology

(1)本发明的负极材料采用多层包覆设计,第一层N/P/B掺杂碳层提供电子导电基础,第二层含镁的锂铝氧化物层利于锂离子的传输,最外层含氟碳材料在兼顾电子导电的同时,在充放电过程中参与形成SEI膜。三层结构配合,可降低电荷转移阻抗,改善材料的综合电化学性能。

✦ Generated by Eureka AI based on patent content.

Smart Images

  • Figure SMS_1
    Figure SMS_1
Patent Text Reader

Abstract

The application relates to the technical field of new energy materials and devices, in particular to a negative electrode material for a lithium ion battery and a preparation method and application thereof. The negative electrode material comprises a natural spherical graphite core, an inner layer of N / P / B ternary doped amorphous carbon layer for improving electronic conductivity and modifying surface defects, a middle layer of magnesium-containing lithium aluminum oxide nanometer film for promoting lithium ion transmission, and an outer layer of a fluorine-containing nanometer carbon material and a polymer binder crosslinked and compounded hydrophobic conductive layer for improving water-based slurry stability and participating in the construction of a stable SEI film. The first coulomb efficiency of the material can reach more than 92.5%, the 3C rate retention rate is more than 84%, and the 300-cycle retention rate is higher than 93%, so that the material is suitable for high-power and long-life lithium ion batteries.
Need to check novelty before this filing date? Find Prior Art

Description

Technical Field

[0001] This invention relates to the field of new energy materials and devices, specifically to negative electrode materials for lithium-ion batteries, their preparation methods, and applications. Background Technology

[0002] With the continuous development of new energy vehicles and energy storage technologies, higher requirements are being placed on the energy density, rate performance, and cycle life of lithium-ion batteries. Natural graphite, due to its high specific capacity, low cost, and wide availability, is currently the most mature commercially applicable anode material for lithium-ion batteries.

[0003] However, natural graphite still has some limitations in practical applications. On the one hand, the surface of natural graphite has many edge defects, which can easily trigger side reactions during the first charge and discharge process, consuming active lithium and leading to a decrease in the first coulombic efficiency. On the other hand, the layered structure of natural graphite causes lithium ions to be inserted mainly from the material end faces, resulting in a longer diffusion path and affecting rate performance. To improve these problems, researchers have tried various surface modification strategies.

[0004] Chinese patent application CN114497546A, published on May 13, 2022, discloses a graphite anode material. This material forms a carbon coating layer containing B, N, and P modified groups on the surface of spherical graphite. By introducing specific groups, it reduces side reactions between the coating layer and the electrolyte, thereby improving the initial coulombic efficiency and cycle expansion performance. However, this approach only involves a single-layer carbon coating layer, and the optimization of the lithium-ion diffusion path remains limited.

[0005] Chinese patent application CN116314638A, published on June 23, 2023, discloses a composite anode material in which a connecting layer and a carbon layer are sequentially formed on the surface of a graphite core. Both the connecting layer and the carbon layer contain amorphous carbon doped with elements such as N, P, B, and F, with the dopant content in the connecting layer being higher than that in the carbon layer. This scheme improves rate performance and low-temperature performance through gradient doping design, but its structure is still limited to two carbon coating layers and does not involve the design of an independent ion conduction layer.

[0006] Chinese patent applications CN106505199A (published March 15, 2017) and CN108134044A (published June 8, 2018) both incorporate lithium aluminate (LiAlO2) as a lithium-ion conduction enhancing component in the graphite surface coating layer. However, in these solutions, LiAlO2 is dispersed as an additive within the carbonaceous coating layer rather than functioning as an independent continuous layer, thus its ion conduction efficiency is limited by the carbon matrix.

[0007] Chinese patent application CN117239090A, published on December 15, 2023, discloses a negative electrode material in which a composite layer comprising carbonaceous and non-carbonaceous materials is formed on the surface of a graphite core. The chemical formula of the non-carbonaceous material is A. x B x It may contain elements such as Mg, Al, and O. However, in this scheme, carbonaceous and non-carbonaceous materials are mixed in the same composite layer, without forming a layered structure.

[0008] In addition, Chinese patent application CN119361663A, published on January 24, 2025, discloses that coating the surface of natural graphite with N, O, F / metal heteroatoms co-doped carbon materials helps to form an inorganic LiF-rich SEI film, but it is also limited to a single-layer doped carbon shell structure and does not involve multi-layer functional synergistic design.

[0009] In summary, single-component coatings struggle to achieve a good balance between electronic conductivity, ionic conductivity, and stability in aqueous slurry processing. While various coating schemes exist in the prior art, most are limited to single-layer or double-layer carbonaceous coatings, and the functional division of each layer is unclear. Therefore, there is an urgent need to develop a multi-layer core-shell anode material that, through the synergistic function of each layer, achieves comprehensive performance in terms of electronic conductivity, ionic conductivity, and adaptability to aqueous processing. Summary of the Invention

[0010] In view of the shortcomings of the prior art, the purpose of this invention is to provide a negative electrode material for lithium-ion batteries, which, through the synergistic design of multiple functional layers, takes into account electronic conductivity, ion conduction and adaptability to aqueous processing.

[0011] Another objective of this invention is to provide a method for preparing the above-mentioned negative electrode material. This method employs in-situ coating of liquid-phase precursors and gradient heat treatment processes, resulting in uniform thickness and complete structure of each layer. Furthermore, the corrosion of the oxide layer by the fluorine-containing layer is suppressed at high temperatures, making the method controllable and easy to industrialize.

[0012] The third objective of this invention is to provide a lithium-ion battery containing the above-mentioned negative electrode material, which can achieve a high initial coulombic efficiency, a high high-rate discharge capability, and good long-term cycle stability, and is particularly suitable for power batteries and energy storage systems with high power density and lifespan requirements.

[0013] This invention is achieved using the following technical solution: The aforementioned negative electrode material for lithium-ion batteries includes: The core body is natural spherical graphite; The first coating layer, which coats the surface of the core, is an N / P / B ternary doped amorphous carbon layer; The second coating layer, which is coated on the surface of the first coating layer, is a magnesium-containing lithium aluminum oxide layer; The third coating layer, which covers the surface of the second coating layer, is a carbon layer containing fluorine.

[0014] Furthermore, the median diameter (D50) of the core-forming natural spherical graphite is 10-20 μm, and the specific surface area is 2.0-5.0 m². 2 / g.

[0015] Choosing natural spherical graphite of this size and specific surface area range as the core material can take into account the compaction density of the negative electrode sheet and provide a suitable surface area basis for multi-layer coating.

[0016] Furthermore, in the negative electrode material, the mass fraction of N element is 0.1-2.0%, the mass fraction of P element is 0.1-1.5%, and the mass fraction of B element is 0.05-1.0%.

[0017] The introduction of N, P, and B elements into the inner carbon layer helps to improve the electronic conductivity of the carbon layer; P helps to moderately increase the local interlayer spacing of carbon microcrystals, which is beneficial to lithium ion diffusion; and B, as an electron-deficient element, helps to modify some active sites on the surface of natural graphite and reduce side reactions of the electrolyte on the material surface.

[0018] Furthermore, based on the total mass of the negative electrode material, the mass fraction of Al in the negative electrode material is 0.2-1.5%, and the mass fraction of Mg is 0.005-0.05%.

[0019] Lithium aluminum oxide, used as an intermediate layer, possesses good ion conductivity. The thin film structure formed by in-situ liquid-phase coating can reduce the physical barrier effect caused by excessive coating thickness.

[0020] Furthermore, the third coating layer is formed by cross-linking fluorinated carbon nanomaterials and polymer binders; the fluorinated carbon nanomaterials are selected from fluorinated graphene or fluorinated carbon nanotubes; the thickness of the first coating layer is 20-200 nm, the thickness of the second coating layer is 5-50 nm, and the thickness of the third coating layer is 10-100 nm.

[0021] Fluorine-containing carbon nanomaterials contain a conductive network structure, and the fluorine on the surface endows the material with low surface energy. When placed as the outermost layer, it provides hydrophobicity during aqueous slurrying; during battery cycling, the surface fluorine participates in the formation of the solid electrolyte interphase (SEI) film, forming an inorganic LiF-containing SEI film, which improves interfacial stability.

[0022] The second aspect of the present invention is a method for preparing the above-mentioned negative electrode material for lithium-ion batteries, comprising the following steps: S1: A compound containing N, P, and B elements and a carbon source are dispersed in a solvent, and an organic amine catalyst is added to react and obtain a precursor composite gel. S2: The precursor composite gel obtained in step S1 is mixed with natural spherical graphite, dried and desolventized, and then subjected to a first heat treatment to obtain an intermediate product with an N / P / B ternary doped amorphous carbon layer on the surface; the conditions for the first heat treatment are: under an inert atmosphere, at 800-1000℃ for 1-4 hours. S3: Dissolve soluble lithium, aluminum, and magnesium sources in a solvent, add a complexing agent, and form a uniform magnesium-lithium-aluminum oxide precursor sol; the complexing agent is selected from citric acid, oxalic acid, ethylenediaminetetraacetic acid, or tartaric acid, and its amount is 0.5-2.0 times the total molar amount of metal ions; S4: Mix the precursor sol obtained in step S3 with the intermediate product obtained in step S2, remove the solvent to coat the precursor onto the particle surface, and then perform a second heat treatment to crystallize the precursor in situ to form a magnesium-containing lithium aluminum oxide layer. S5: Disperse the fluorine-containing carbon nanomaterial and polymer binder in a solvent, mix with the product obtained in step S4, remove the solvent, and then perform a third low-temperature heat treatment to form a film, thereby obtaining the negative electrode material.

[0023] Further, in step S1, the compounds containing N, P, and B elements and the carbon source include phytic acid, melamine, boric acid, and pyromellitic dianhydride; the organic amine catalyst is selected from triethylamine, pyridine, or N,N-dimethylethanolamine, and its addition amount is 1-5% of the molar amount of pyromellitic dianhydride.

[0024] Using organic amines as catalysts can promote the ring-opening and polymerization reactions of acid anhydrides, which is beneficial for the formation of cross-linked structures.

[0025] Furthermore, in steps S3 and S4, liquid-phase precursor sol mixing and a second heat treatment at 650-750℃ are employed.

[0026] Compared to solid-phase powder mixing, the sol-gel method using liquid-phase precursors can form a uniformly distributed coating precursor on the surface of micron-sized graphite particles, which is then transformed in situ into a continuous oxide coating layer after subsequent heat treatment.

[0027] Further, in step S5, the polymer binder is selected from polyimide precursor or phenolic resin, and its addition amount is 0.1-0.5% of the mass of the core natural spherical graphite; the conditions for the third low-temperature heat treatment are: under an inert atmosphere, heat treatment at 300-450℃ for 1-3 hours.

[0028] The final heat treatment temperature is controlled in the medium-low temperature range of 300-450℃. This condition allows the polymer binder to complete the curing and film formation, and allows the fluorinated carbon nanomaterials to adhere to the particle surface. At the same time, this temperature is lower than the violent thermal decomposition temperature of conventional fluorinated carbon sources, which can reduce the release of hydrogen fluoride (HF) gas, thereby reducing the corrosion of the intermediate layer of magnesium lithium aluminum oxide and maintaining the integrity of the multilayer structure.

[0029] The third aspect of the present invention is a lithium-ion battery, comprising a positive electrode, an electrolyte, a separator, and a negative electrode, wherein the negative electrode comprises the aforementioned negative electrode material for lithium-ion batteries, or comprises a negative electrode material for lithium-ion batteries obtained by the aforementioned preparation method.

[0030] Compared with the prior art, the beneficial effects of the present invention are: (1) The negative electrode material of the present invention adopts a multilayer coating design. The first layer, an N / P / B doped carbon layer, provides the basis for electronic conductivity. The second layer, a magnesium-containing lithium aluminum oxide layer, facilitates the transport of lithium ions. The outermost layer, a fluorinated carbon material, not only ensures electronic conductivity but also participates in the formation of the SEI film during charging and discharging. The three-layer structure can reduce charge transfer impedance and improve the overall electrochemical performance of the material.

[0031] (2) The present invention introduces a low surface energy fluorine-containing nano-carbon layer on the outermost layer, which can reduce the direct contact between water and the inner lithium-rich layer, thereby inhibiting the dissolution of active lithium in the water-based pulping process, reducing the fluctuation of the slurry pH value, and helping to maintain the stability of the electrode coating process.

[0032] (3) The use of liquid phase in-situ coating combined with medium and low temperature crosslinking curing process can improve the uniformity of the coating layer and reduce the problem that conventional high temperature fluorine carbide sources may release corrosive gases and thus affect the crystal structure of the inner oxide layer. This process route can stably prepare the required multilayer structure material. Detailed Implementation

[0033] To enable those skilled in the art to better understand the technical solutions of the present invention, the present invention will be further described in detail below with reference to specific embodiments and comparative examples. It should be understood that the specific embodiments described herein are only for explaining the present invention and are not intended to limit the scope of protection of the present invention. Conventional adjustments or substitutions made by those skilled in the art based on the content disclosed in the present invention without departing from the design concept of the present invention are all within the scope of protection of the present invention.

[0034] To achieve the multi-layered core-shell structure described in the claims of this invention, those skilled in the art must follow the following process logic and constraints during implementation: (1) Atmosphere control: The three heat treatment processes involved in this invention (including carbonization, in-situ crystallization and cross-linking curing) must be carried out under an inert atmosphere (such as high-purity nitrogen or argon) to avoid oxidation and burn-off of the carbon layer at high temperature.

[0035] (2) Coating uniformity: In the mixing and desolvation process in steps S2 and S4, it is advisable to use a stirring device with ultrasonic assistance or high-speed shearing function, and combine it with rotary evaporation or spray drying process to ensure that the precursor forms a film of uniform thickness on the surface of micron-sized graphite particles, and avoid macroscopic agglomeration of the precursor.

[0036] (3) Temperature gradient setting: The first N / P / B doped carbon layer has a relatively high calcination temperature (usually 800-1000℃) to achieve full carbonization of the carbon source and doping of heteroatoms; the second oxide layer has a moderate crystallization temperature (650-750℃) to promote the formation of crystal structures of Li, Al, and Mg elements without causing significant changes in the internal carbon layer structure; the third layer has the lowest curing temperature (300-450℃) to achieve cross-linking of polymer precursors and reduce the possibility of thermal decomposition side reactions of fluorinated materials at high temperatures. The process parameters of each layer decrease from the inside to the outside, which is thermodynamically beneficial to the compatibility and integrity of the multilayer structure.

[0037] The main chemical reagents and materials used in the embodiments and comparative examples of this invention are sourced from the following sources, all of which are commercially available conventional products: Natural spherical graphite: Shenzhen BTR New Energy Materials Co., Ltd., battery-grade products with specifications of D50=15μm and D50=10μm.

[0038] Fluorinated carbon nanomaterials: Fluorinated graphene (F-rGO, fluorine content approximately 47~60 wt.%, sheet diameter 0.4~10 μm) and fluorinated carbon nanotubes (F-CNTs, fluorine content approximately 48~58 wt.%), both from Nanjing Xianfeng Nanomaterials Technology Co., Ltd.

[0039] Polymer binders: Polyimide (PI) precursor (polyamic acid solution, solid content 15%) Sinopharm Chemical Reagent Co., Ltd.; Phenolic resin (thermosetting, industrial grade) Shandong Shengquan New Material Co., Ltd.

[0040] Inorganic salts and compounds: lithium acetate, aluminum isopropoxide, magnesium acetate, phytic acid (70% aqueous solution), melamine, boric acid, pyromellitic dianhydride (PMDA), citric acid, etc., all from Sinopharm Chemical Reagent Co., Ltd., analytical grade (AR) or higher.

[0041] Solvents and catalysts: N-methylpyrrolidone (NMP, battery grade), anhydrous ethanol (AR), triethylamine (AR), etc., all from Sinopharm Chemical Reagent Co., Ltd.; deionized water (resistivity ≥18.2 MΩ·cm).

[0042] Battery auxiliary materials: Conductive carbon black (Super P) from Swiss company Erystal; Sodium carboxymethyl cellulose (CMC) from Nippon Paper; Styrene-butadiene rubber (SBR) from Zeon, Japan.

[0043] Electrolyte: 1.0 M LiPF6, solvent EC:DEC=1:1 v / v, containing 5% FEC additive, Guangzhou Tinci Advanced Materials Co., Ltd.

[0044] Lithium nitrate (LiNO3), tetrabutyl titanate (C 16 Both H6O4Ti and ammonium dihydrogen phosphate (NH4H2PO4) are analytical grade reagents, manufactured by Sinopharm Chemical Reagent Co., Ltd.

[0045] Testing instruments: Powder resistivity meter (Suzhou Jingge Electronics Co., Ltd., model ST2722-SZ or ST2722-SD); pH meter (Mettler-Toledo Instruments (Shanghai) Co., Ltd., model FE28, FiveEasy Plus series); Electrochemical workstation (Shanghai Chenhua Instruments Co., Ltd., model CHI660E).

[0046] To objectively evaluate the physicochemical and electrochemical properties of the negative electrode materials prepared in each embodiment and comparative example, the following standardized test methods were used: Powder conductivity test Referring to the method for determining powder conductivity in GB / T 24533-2019, a powder resistivity tester (Suzhou Jingge Electronics, ST2722 model) was used. 2.0 g of sample was weighed and placed in the test mold. A constant pressure of 12 MPa was applied and held for 10 s until the resistance value stabilized. The volume resistivity of the powder was then measured. The powder conductivity (S / cm) was calculated using the formula σ = L / (R·S), where L is the sample thickness (cm), R is the resistance value (Ω), and S is the electrode cross-sectional area (cm²). 2 Each sample was tested in triplicate, and the average value was taken.

[0047] pH stability test of aqueous slurry (ΔpH) Following the method in Appendix C of GB / T 24533-2019, 5.0 g of the negative electrode material powder to be tested was weighed and added to 50 mL of boiled and cooled deionized water (conductivity <2 μS / cm). The mixture was then placed in a planetary gravity mixer and stirred at 1500 rpm for 15 minutes to prepare a homogeneous suspension. The initial pH value was measured immediately after stirring using a glass electrode pH meter (Mettler-Toledo, FiveEasy Plus type) calibrated at three points with standard buffer solutions of pH 4.00, 6.86, and 9.18. The suspension was then allowed to stand in a sealed environment at 25°C for 24 hours, and the pH value was measured again. The difference in pH value before and after standing was calculated and recorded as ΔpH. Each sample was tested in triplicate, and the average value was taken.

[0048] Specific surface area test The determination was performed according to GB / T 19587 "Determination of Specific Surface Area of ​​Solid Substances by Gas Adsorption BET Method". A low-temperature nitrogen adsorption BET multi-point method was used. Before testing, the sample was degassed at 200℃ for at least 2 hours. The nitrogen adsorption amount was measured at different relative pressures at 77K liquid nitrogen temperature. The specific surface area (m²) of the sample was calculated using the BET formula. 2 / g). Each sample was tested in triplicate, and the average value was taken.

[0049] Button cell assembly and electrochemical performance testing Electrode preparation: The negative electrode material to be tested, conductive agent, thickener, and binder were mixed at a mass ratio of 95:1.5:1.5:2. An appropriate amount of deionized water was added to adjust the viscosity. After stirring evenly, the mixture was coated onto a 9 μm thick copper foil. After drying in a vacuum oven at 110℃ for 12 hours, the mixture was cut into 12 mm diameter discs and compacted using a roller mill (compaction density controlled at 1.55~1.60 g / cm³). 3 ).

[0050] Battery Assembly: CR2032 coin cells were assembled in a glove box filled with high-purity argon (water and oxygen content <0.1 ppm). A lithium metal sheet (15.6 mm in diameter) was used as the counter electrode, and a Celgard 2400 microporous polypropylene membrane (19 mm in diameter) was used as the separator. 80 μL of electrolyte (1.0 M LiPF6, solvent EC:DEC = 1:1 v / v, containing 5% FEC additive) was injected.

[0051] Charge / discharge test: The test was conducted using the Xinwei CT-4008T battery testing system, with the voltage window set to 0.01~1.5V (vs. Li / Li). + ).

[0052] First coulombic efficiency (ICE): Under 0.1C rate, the first round of constant current and constant voltage discharge (lithiation, to 0.01V, cutoff current 0.02C) and constant current charging (lithiation removal, to 1.5V) are performed. The ratio of the first round of lithium removal capacity to the first round of lithium insertion capacity is calculated, i.e., ICE (%) = first round of lithium removal capacity / first round of lithium insertion capacity × 100%.

[0053] High rate retention rate: After three constant current charge-discharge cycles at 0.2C, the discharge rate is increased to 3C (the charge rate is kept at 0.5C). The average discharge capacity of the last three cycles at 3C is recorded. The ratio of the average discharge capacity of the last three cycles at 0.2C is the 3C rate retention rate (%).

[0054] Cycling performance: Under 1C charge / 1C discharge conditions, 300 cycles are performed. The ratio of the discharge capacity of the 300th cycle to the discharge capacity of the 1st 1C cycle is calculated, which is the 1C cycle retention rate (%).

[0055] Electrochemical Impedance Spectroscopy (EIS) Testing: Using an electrochemical workstation (Shanghai Chenhua, CHI660E), after the coin cell half-cell was activated, the cell was charged (delithiated) to 1.5 V (delithiated state, i.e., negative electrode unloaded state), and the test was conducted at 25±2℃. The test frequency range was 1 MHz to 0.01 Hz, and the AC amplitude was 5 mV. The Nyquist plot was fitted with an equivalent circuit using ZView software, and the impedance values ​​corresponding to the semicircles in the high-frequency region (including SEI film impedance and contact impedance, denoted as R) were read. SEI ) and the charge transfer impedance corresponding to the semicircle in the mid-frequency region (denoted as R) ct Five parallel cells were assembled for each sample and tested, and the average value was taken.

[0056] Example 1 The preparation of a multilayer core-shell structured lithium-ion battery anode material includes the following steps: (1) Preparation of the first coating layer: Take 200 mL of N-methylpyrrolidone (NMP), add 2.5 g of phytic acid (70% aqueous solution), 1.8 g of melamine, 1.0 g of boric acid and 10.0 g of pyromellitic dianhydride (PMDA) in sequence, stir evenly, add 3% (approximately 0.45 g) of triethylamine relative to the molar amount of PMDA as an organic amine catalyst, stir and react at 90 °C for 2 hours to obtain the precursor composite gel. Mix 100 g of natural spherical graphite with a D50 of 15 μm with the above gel, remove the solvent by vacuum drying, and calcine at 900 °C for 2 hours under nitrogen protection to obtain intermediate product A1 with an N / P / B doped amorphous carbon layer on the surface.

[0057] (2) Preparation of the second coating layer: 6.0 g of lithium acetate, 17.0 g of aluminum isopropoxide and 0.35 g of magnesium acetate were dissolved in 200 mL of ethanol-water solution (ethanol:water = 1:1, volume ratio). 8.0 g of citric acid was added as a complexing agent, and the mixture was stirred at 60 °C to form a uniform magnesium-lithium-aluminum oxide precursor sol. Intermediate product A1 was added to the sol, stirred, and the solvent was evaporated. Then, the mixture was heated to 700 °C and held for 2.5 hours under argon protection to allow it to crystallize in situ, yielding intermediate product B1.

[0058] (3) Preparation of the third coating layer: 1.0 g of fluorinated graphene (F-rGO) and 0.74 g of polyimide (PI) precursor (solid content 15%) (equivalent to approximately 0.111 g of PI precursor solid content, or 0.11% of graphite mass) were dispersed in 50 mL of NMP. Intermediate product B1 was added and mixed evenly. After drying to remove the solvent, the mixture was kept at 400 °C for 2 hours under a nitrogen atmosphere to allow the binder to crosslink and cure. After cooling to room temperature, the target anode material was obtained.

[0059] Elemental analysis revealed that the mass fractions of N, P, and B in the material were 0.8%, 0.6%, and 0.3%, respectively; while the mass fractions of Al and Mg were 0.8% and 0.02%, respectively.

[0060] Example 2 This embodiment is basically the same as that of Embodiment 1, except that in step (3): 1.0g of fluorinated carbon nanotubes (F-CNTs) is used to replace fluorinated graphene, and 0.12g of phenolic resin (equivalent to 0.12% of the graphite mass) is used to replace the polyimide precursor. The crosslinking and curing temperature is set to 350℃ and held for 2 hours. The remaining raw material ratios and process conditions are the same as those in Embodiment 1.

[0061] Example 3 This embodiment is basically the same as Embodiment 1, except that in step (1): the amount of phytic acid (70% aqueous solution) is adjusted to 5.6g, the amount of melamine is adjusted to 4.2g, and the amount of boric acid is adjusted to 2.6g, so that the mass fractions of N, P, and B in the final negative electrode material are increased to 1.8%, 1.2%, and 0.8%, respectively. The remaining raw material ratios and process conditions are the same as in Embodiment 1.

[0062] Example 4 This embodiment is basically the same as that of embodiment 1, except that in step (2): the amount of lithium acetate is adjusted to 6.0g, the amount of aluminum isopropoxide is adjusted to 8.5g, and the amount of magnesium acetate is adjusted to 0.70g, so that the mass fraction of Al in the final product is 0.4% and the mass fraction of Mg is 0.04%. The other raw material ratios and process conditions are the same as those in embodiment 1.

[0063] Example 5 This embodiment is basically the same as Embodiment 1, except that in step (1): the selected natural spherical graphite has a D50 of 10 μm and a specific surface area of ​​4.5 m². 2 / g, the dosage remains 100g. The proportions of other raw materials and process conditions are consistent with those in Example 1.

[0064] Comparative Example 1 Natural spherical graphite from the same batch as in Example 1, without any coating treatment, was used as Comparative Example 1.

[0065] Comparative Example 2 Compared with Example 1, step (3) is omitted in this comparative example. That is, the material only contains "graphite core + N / P / B carbon layer + Mg-doped lithium aluminum oxide layer", and the outermost layer is directly exposed as an oxide layer.

[0066] Comparative Example 3 Compared with Example 1, this comparative example omits step (2). That is, the material contains "graphite core + N / P / B carbon layer + fluorinated carbon layer", but lacks an ion-conducting intermediate layer.

[0067] Comparative Example 4 Compared with Example 1, this comparative example omits step (1). That is, a Mg-doped lithium aluminum oxide layer and a fluorocarbon layer are directly coated onto the surface of bare graphite in sequence.

[0068] Comparative Example 5 This comparative example is basically the same as Example 1, except that in step (1): pyromellitic dianhydride (PMDA) and organic amine catalysts are not used, and only conventional glucose is used as a carbon source to physically mix and sinter with phytic acid, melamine and boric acid.

[0069] Comparative Example 6 This comparative example is basically the same as Example 1, except that in step (2): magnesium acetate is not added, and only a pure phase lithium aluminum oxide (LiAlO2) intermediate layer is prepared.

[0070] Comparative Example 7 The structural design of this comparative example is similar to that of Example 1, but the process of step (3) is changed: conventional fluorinated asphalt (Shandong Zhongshan Optoelectronic Materials Co., Ltd., fluorine content ≥45wt%, softening point 120℃) is used instead of fluorinated graphene, and the temperature of the third heat treatment is increased to 600℃ to achieve carbonization of the asphalt.

[0071] Comparative Example 8 This comparative example is basically the same as Example 1, except that in step (2): the amount of magnesium acetate added is increased so that the mass fraction of Mg in the final product reaches 0.15%.

[0072] Comparative Example 9 This comparative example is basically the same as Example 1, except that in step (2): the magnesium-containing lithium aluminum oxide precursor sol is replaced with the conventional fast ion conductor LATP (NASICON type, Li 1.4 Al 0.4 Ti 1.6 (PO4)3) precursor sol. Lithium nitrate, aluminum isopropoxide, tetrabutyl titanate and ammonium dihydrogen phosphate were dissolved in a mixed solvent in stoichiometric ratio to form a sol, which was then crystallized in situ at the same temperature (700°C). The rest of the process was the same as in Example 1.

[0073] Comparative Example 10 This comparative example is basically the same as Example 1, with completely identical raw materials and proportions. The only difference is in step (3): the temperature of the third heat treatment is increased from 400°C to 650°C, so that the system undergoes a conventional high-temperature treatment process.

[0074] Comparative Example 11 This comparative example is basically the same as Example 1, except that in step (1): boric acid is not added, and only phytic acid and melamine are used as P source and N source to prepare intermediate product A1 containing only N / P double doped amorphous carbon layer, while the rest of the process remains unchanged.

[0075] The physicochemical and electrochemical performance test results of Examples 1-5 and Comparative Examples 1-11 are shown in Table 1.

[0076] Table 1: Physicochemical and electrochemical performance test results of Examples 1-5 and Comparative Examples 1-11

[0077] As shown in Table 1, the overall performance of Examples 1-5 of the present invention is superior to that of the comparative examples. Example 1 exhibits high initial coulombic efficiency, 3C rate retention, and 300-cycle retention, with a slurry ΔpH of 0.18, indicating that the three-layer structure synergistically contributes to electronic conductivity, ion conduction, and waterproofing and hydrolysis resistance. Comparative Example 2, lacking an outer fluorinated layer, has a ΔpH of 2.15, significantly higher than the examples, indicating that the outer fluorinated layer improves the stability of the aqueous slurry. Comparative Example 3, lacking an intermediate oxide layer, has a charge transfer impedance Rct of 38.5 Ω and a rate retention of 72.5%, demonstrating that the intermediate oxide layer contributes to reducing interfacial impedance and improving rate performance. Comparative Example 4, lacking an inner doped carbon layer, has lower electronic conductivity and initial coulombic efficiency, indicating that the inner doped carbon layer contributes to electronic conductivity and suppresses side reactions. Comparative Example 5, which did not use a crosslinking precursor, had a lower cycle retention rate than Example 1, indicating that the crosslinking precursor plays a role in improving cycle stability. Comparative Example 6, which did not undergo Mg doping, had a lower 3C rate retention rate than Example 1, but a higher Rct, indicating that Mg doping improves rate performance. Comparative Example 7, which used high-temperature fluorinated asphalt, had all its properties lower than Example 1, with an Rct as high as 65.2 Ω, possibly related to the release of corrosive gases from fluorinated substances at high temperatures. Comparative Example 8, with a Mg content exceeding the limits defined in this invention, had a significantly lower 3C rate retention rate than Example 1, indicating that excessively high Mg content has an adverse effect on rate performance. Comparative Example 9, which used LATP instead of Mg-containing lithium aluminum oxide as the intermediate layer, had both its initial coulombic efficiency and 3C rate retention rate lower than Example 1, indicating that Mg-containing lithium aluminum oxide as the intermediate layer has better compatibility in this system. Comparative Example 10, which increased the third heat treatment temperature to 650°C, showed a deterioration in all its properties, indicating that medium- and low-temperature heat treatment is significant for maintaining the structural integrity of the material. Comparative Example 11, without the addition of a B source, had an initial coulombic efficiency of 91.0%, lower than that of Example 1 (93.2%), indicating that B doping has an effect on improving the initial coulombic efficiency.

Claims

1. A negative electrode material for lithium-ion batteries, characterized in that, include: The core body is natural spherical graphite; The first coating layer, which coats the surface of the core, is an N / P / B ternary doped amorphous carbon layer; The second coating layer, which is coated on the surface of the first coating layer, is a magnesium-containing lithium aluminum oxide layer; The third coating layer, which covers the surface of the second coating layer, is a carbon layer containing fluorine.

2. The negative electrode material for lithium-ion batteries according to claim 1, characterized in that, The core of the natural spherical graphite has a D50 of 10-20 μm and a specific surface area of ​​2.0-5.0 m². 2 / g.

3. The negative electrode material for lithium-ion batteries according to claim 1, characterized in that, In the negative electrode material, the mass fraction of N element is 0.1-2.0%, the mass fraction of P element is 0.1-1.5%, and the mass fraction of B element is 0.05-1.0%.

4. The negative electrode material for lithium-ion batteries according to claim 1, characterized in that, Based on the total mass of the negative electrode material, the mass fraction of Al in the negative electrode material is 0.2-1.5%, and the mass fraction of Mg is 0.005-0.05%.

5. The negative electrode material for lithium-ion batteries according to claim 1, characterized in that, The third coating layer is composed of a cross-linked composite of fluorinated carbon nanomaterials and a polymer binder; the fluorinated carbon nanomaterials are selected from fluorinated graphene or fluorinated carbon nanotubes; the thickness of the first coating layer is 20-200 nm, the thickness of the second coating layer is 5-50 nm, and the thickness of the third coating layer is 10-100 nm.

6. A method for preparing a negative electrode material for lithium-ion batteries according to any one of claims 1-5, characterized in that, Includes the following steps: S1: A compound containing N, P, and B elements and a carbon source are dispersed in a solvent, and an organic amine catalyst is added to react and obtain a precursor composite gel. S2: The precursor composite gel obtained in step S1 is mixed with natural spherical graphite, dried and desolventized, and then subjected to a first heat treatment to obtain an intermediate product with an N / P / B ternary doped amorphous carbon layer on the surface; the conditions for the first heat treatment are: under an inert atmosphere, at 800-1000℃ for 1-4 hours. S3: Dissolve soluble lithium, aluminum, and magnesium sources in a solvent, add a complexing agent, and form a uniform magnesium-lithium-aluminum oxide precursor sol; the complexing agent is selected from citric acid, oxalic acid, ethylenediaminetetraacetic acid, or tartaric acid, and its amount is 0.5-2.0 times the total molar amount of metal ions; S4: Mix the precursor sol obtained in step S3 with the intermediate product obtained in step S2, remove the solvent to coat the precursor onto the particle surface, and then perform a second heat treatment to crystallize the precursor in situ to form a magnesium-containing lithium aluminum oxide layer. S5: Disperse the fluorine-containing carbon nanomaterial and polymer binder in a solvent, mix with the product obtained in step S4, remove the solvent, and then perform a third low-temperature heat treatment to form a film, thereby obtaining the negative electrode material.

7. The method for preparing the negative electrode material for lithium-ion batteries according to claim 6, characterized in that, In step S1, the compound containing N, P, and B elements and the carbon source include phytic acid, melamine, boric acid, and pyromellitic dianhydride; the organic amine catalyst is selected from triethylamine, pyridine, or N,N-dimethylethanolamine, and its addition amount is 1-5% of the molar amount of pyromellitic dianhydride.

8. The method for preparing the negative electrode material for lithium-ion batteries according to claim 6, characterized in that, In step S3, the soluble lithium source is selected from lithium acetate or lithium nitrate, the aluminum source is selected from aluminum isopropoxide or aluminum nitrate, and the magnesium source is selected from magnesium acetate or magnesium nitrate. In step S4, the conditions for the second heat treatment are: under an inert atmosphere, the temperature is raised to 650-750℃ and held for 2-3 hours.

9. The method for preparing the negative electrode material for lithium-ion batteries according to claim 6, characterized in that, In step S5, the polymer binder is selected from polyimide precursor or phenolic resin, and its addition amount is 0.1-0.5% of the mass of the core natural spherical graphite; the conditions for the third low-temperature heat treatment are: under an inert atmosphere, heat treatment at 300-450℃ for 1-3 hours.

10. A lithium-ion battery, characterized in that, It includes a positive electrode, an electrolyte, a separator, and a negative electrode, wherein the negative electrode comprises a negative electrode material for lithium-ion batteries as described in any one of claims 1-5, or comprises a negative electrode material for lithium-ion batteries obtained by the preparation method described in any one of claims 6-9.

Citation Information

Patent Citations

  • Composite anode material for lithium ion battery, preparation method of composite anode material and lithium ion battery

    CN106505199A

  • High-safety lithium ion battery anode material and preparation method thereof

    CN108134044A

  • Graphite negative electrode material, preparation method thereof and lithium ion battery

    CN114497546A

  • Composite negative electrode material, preparation method thereof and lithium ion battery

    CN116314638A

  • Negative electrode material, preparation method thereof and lithium ion battery

    CN117239090A